2009
DOI: 10.1111/j.1365-2893.2009.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy and antiviral treatment for thrombocytopenic patients with chronic hepatitis C virus infection

Abstract: Thrombocytopenic patients with chronic hepatitis C virus (HCV) infection are poor candidates for antiviral treatment with interferon (IFN), but no standard treatment for thrombocytopenia has yet been established. We evaluated the safety of splenectomy and its efficacy for the initiation and continuation of antiviral therapy. From March 2003 to April 2006, 10 patients (mean age 62.5 years) with HCV-related cirrhosis, low platelet count (<==106 000/mm(3)) and splenomegaly (spleen size >==10 cm) underwent splenec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Thus, as in prior studies, severe thrombocytopenia did not always exclude IFN-based therapy [20][21][22][23][24][25][26][27]. During IFN-based therapy, platelet counts decreased but did not reach the discontinuance criteria.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Thus, as in prior studies, severe thrombocytopenia did not always exclude IFN-based therapy [20][21][22][23][24][25][26][27]. During IFN-based therapy, platelet counts decreased but did not reach the discontinuance criteria.…”
Section: Discussionmentioning
confidence: 71%
“…A previous study [24] indicated that the SVR rate in patients with genotype 1 was 33%, compared to a rate of 100% in patients with genotype 2. In addition, previous studies of IFN-based therapy after splenectomy [20][21][22] showed that SVR was achieved only in patients with genotypes 2b and 1b with a low viral load. Besides, in our study, it was notable that under the condition that the Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the guidelines indicated splenectomy can be a useful way to increase platelet count for these patients, these studies were small; only a few successful cases reported specifically on these patients whose platelet count was more than 50×10 9 /l, guaranteeing the success of operation [9][10][11][12]. We seldom found case reports in which platelets were as low as below 10×10 9 /l with splenectomy.…”
Section: Discussionmentioning
confidence: 92%